Information Seeking Behavior among the Final Years Students Department of LISAS at the University of Sindh Jamshoro, Pakistan - Inam Magsi; Arif Ali Bhatti; Dr. Muhammad Akhtar Rind (Journal of Peace, Development and Communication, 2024)
Present study investigates the Information Seeking Behavior among the final years students department of LISAS at the University Of Sindh Jamshoro Pakistan the main objectives of the study were 1. To Know how Frequently LIS Student visit library 2, To investigate purpose of seeking information of LIS students and what type of information resources they usually access. 3. To identify which type of information formats used by LIS students. 4. To find out the problems faced by the LIS students while seeking information the study is based on survey method. The researchers have created a well-structured questionnaire after analyzing a number of academic works. The targeted the population consisted of final-year students in the Department of LIS at the University of Sindh Jamshoro. In order to get to the inference. Simple random survey method was used to collect the data. In order to collect the data investigators visited BLIS class rooms and distributed 85 questionnaires and response rate were 100 % The information gathered from the responses was evaluated using Statistical Package for Social Science (SPSS), version 23, to analyze the data. Frequency and percentile technique have been employed to analyze the data. It was revealed from the data that (52 %) of LIS Students visit the library on daily basis, followed by 30 (35 %) who visit the library 2-4 times a week it was also indicated that (52 %) access books as most required information sources, followed by 18 (21%) who access databases while 10 (11 %) mostly access Journal articles, on the response about the statement the information formats used by the LIS Students it was revealed from the data that (47 %) Students use Lecture Notes as a easily available information format while (35 %) students use internet as a convenient information format. Study also reveals the response about problems faced by the participants it was revealed from the data that (47 %) participants indicated that lack of latest information material is the major problem in seminar library faced by the students while (35 %) responded in favor of the statement about inadequate facilities in the library is second major problem. This study will be beneficial for the policy makers, Librarians and HODs of the departments to set different criteria and facilitate for student.